2004
DOI: 10.1073/pnas.0402268101
|View full text |Cite|
|
Sign up to set email alerts
|

T cell deficiency leads to cognitive dysfunction: Implications for therapeutic vaccination for schizophrenia and other psychiatric conditions

Abstract: The effects of the adaptive immune system on the cognitive performance and abnormal behaviors seen in mental disorders such as schizophrenia have never been documented. Here, we show that mice deprived of mature T cells manifested cognitive deficits and behavioral abnormalities, which were remediable by T cell restoration. T cell-based vaccination, using glatiramer acetate (copolymer-1, a weak agonist of numerous self-reactive T cells), can overcome the behavioral and cognitive abnormalities that accompany neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
335
2
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(367 citation statements)
references
References 48 publications
(55 reference statements)
17
335
2
4
Order By: Relevance
“…From a therapeutic standpoint, urging T cells to traffic to the brain via administration of a CNS-related antigen has been shown to exhibit both an antianxiety and antidepressant effect depending on the animal model (Lewitus and Schwartz, 2009;. Along similar lines, T cells have been shown to be essential for normal cognitive function such that T cell-deficient animals exhibit impaired learning and memory as revealed by Morris water maze, Barnes maze, and radial arm maze that can be reversed by the adoptive transfer of T cells (Kipnis et al, 2004;Ziv et al, 2006). Moreover, experiments using RAG-1 knockout mice (that are deficient in mature B and T cells) have revealed that long-term deficiencies in CD4+ T cells are associated with impaired behavioral responses including increased digging and marble-burying activities compared with wild-type mice (Rattazzi et al, 2013).…”
Section: Immunological Mechanismsmentioning
confidence: 93%
“…From a therapeutic standpoint, urging T cells to traffic to the brain via administration of a CNS-related antigen has been shown to exhibit both an antianxiety and antidepressant effect depending on the animal model (Lewitus and Schwartz, 2009;. Along similar lines, T cells have been shown to be essential for normal cognitive function such that T cell-deficient animals exhibit impaired learning and memory as revealed by Morris water maze, Barnes maze, and radial arm maze that can be reversed by the adoptive transfer of T cells (Kipnis et al, 2004;Ziv et al, 2006). Moreover, experiments using RAG-1 knockout mice (that are deficient in mature B and T cells) have revealed that long-term deficiencies in CD4+ T cells are associated with impaired behavioral responses including increased digging and marble-burying activities compared with wild-type mice (Rattazzi et al, 2013).…”
Section: Immunological Mechanismsmentioning
confidence: 93%
“…A decade ago, our laboratory discovered the importance of the self-reactive T cells in the repair of central nervous system (CNS) injury. 5 The protective capacity of autoimmune cells was further shown in several models of CNS pathology including mechanical injury, 5,6 Alzheimer's disease, 7 Parkinson's disease 8 and imbalances in neurotransmitter levels, 9 as well as non-CNS processes such as skin wound healing. 10 The neuroprotective immune response is a physiological response that is spontaneously evoked after trauma.…”
Section: Introductionmentioning
confidence: 99%
“…6,12,13 In addition to the role of CNSspecific T cells in CNS repair, our group has found that adaptive immune cells are key players in CNS maintenance under nonpathological conditions, especially in hippocampal plasticity. 9,14 We showed that autoreactive T cells are needed to support hippocampal-dependent learning and memory tasks, as well as for the regulation of adult hippocampal neurogenesis and neurotrophic factor production, 14 possibly by regulating microglial phenotype. 15 Adaptive immunity in coping with mental stress Recently, we found an association between T cells and adaptation to psychological stress.…”
Section: Introductionmentioning
confidence: 99%
“…In models of general immune deficiency, impairment in cognitive function has been shown (22), and Brynskikh et al (23) described a role for T cells in cognition and behavior. In neither case, however, a potential relation to adult neurogenesis has been addressed.…”
mentioning
confidence: 99%